2001
DOI: 10.1002/pros.1074.abs
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of curcumin in human prostate cancer. III. Curcumin inhibits proliferation, induces apoptosis, and inhibits angiogenesis of LNCaP prostate cancer cells in vivo

Abstract: BACKGROUND. Earlier work from our laboratory highlighted the therapeutic potential of curcumin (turmeric), used as a dietary ingredient and as a natural anti-in¯ammatory agent in India and other Southeast Asian countries. This agent was shown to decrease the proliferative potential and induce the apoptosis potential of both androgen-dependent and androgenindependent prostate cancer cells in vitro, largely by modulating the apoptosis suppressor proteins and by interfering with the growth factor receptor signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 7 publications
2
66
0
4
Order By: Relevance
“…cell lines (22)(23)(24)(25)(26)(27). In animal studies, curcumin was shown to induce regression of prostate cancer xenografts Mice in nude mice (28). There is also some evidence suggesting that curcumin is antiangiogenic (29,30) and may en-Male Balb/c nude mice between 6 and 8 weeks of age were obtained from the National Cancer Institute hance the anticancer activity of chemotherapy or reduce its toxicity (31,32).…”
Section: Introductionmentioning
confidence: 99%
“…cell lines (22)(23)(24)(25)(26)(27). In animal studies, curcumin was shown to induce regression of prostate cancer xenografts Mice in nude mice (28). There is also some evidence suggesting that curcumin is antiangiogenic (29,30) and may en-Male Balb/c nude mice between 6 and 8 weeks of age were obtained from the National Cancer Institute hance the anticancer activity of chemotherapy or reduce its toxicity (31,32).…”
Section: Introductionmentioning
confidence: 99%
“…5 The biological effect of curcumin and its recently identified targets like NFκB, beta-catenin have been reviewed in detail. 6,7 Laboratory studies have shown the effectiveness of curcumin in prostate cancer chemoprevention both by using in vitro and in vivo models. [8][9][10] Recently synergism in the inhibition of growth of PC3 prostate tumor xenografts in nude mice was demonstrated with curcumin in combination with phenethyl isothiocyanate.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibits endothelial cell proliferation and migration [123] Inhibits tumor microvessels in prostate tumor xenograft [20] Decreases VEGF expression [110,124] Curcumin Turmeric Decreases iNOS and VEGF expression [61,95,110] Inhibits microvessels density in LNCaP prostate and HepG2 liver tumor xenografts [95,137] Indole-3-carbinol Cruciferous vegetables…”
Section: Effect Of Bioactive Agents On Inos Regulatory Mechanismsmentioning
confidence: 99%